Gramsci and Educating the Educator - Del Roio, Marcos [UNESP] (My University, 2022)
The creation of the L'Ordine Nuovo journal took place in a turbulent transition that shook Europe and Italy at the end of the imperialist war of 1914–1918. Established in a humanist literary culture, with emphasis on Benedetto Croce’s influence, the journal’s founders—with Gramsci’s lead—perceived the need to participate in the revolutionary process taking place in the continent.